To speak is to fight - Stefan Sonderling (Communicare)
This article, as part of a larger study on the role of war as the primary and primordial formative mechanism of human thought and communication, investigates the functions of war in the thinking of postmodern philosopher Jean-Francois Lyotard. It is argued that the central idea that provides the structuring framework for Lyotard’s theory of communication is the concept of agonistics that is derived from Heraclitus’ assertion that war is the father of all things. Against the prevailing hegemony of the pacifist bias in poststructuralist social theories, Lyotard returns language to its pragmatic origin in the war-like agonistic and combative social reality. Lyotard’s insight that acts of speaking in society resemble fighting facilitates a better understanding of the contemporary postmodern global world that resembles a return of the neomedieval condition, which was characterised by perfect communication and warfare.